Seberapa Besar Sustainability Report dan Debt to Asset Ratio Mempengaruhi Risiko Financial Distress? Peran Ukuran Perusahaan Sebagai Moderasi - Muhammad Rizki Rahmansyah; Chairil Afandy (STIE Indonesia Banking School, 2025)
This study aims to evaluate the impact of sustainability reports and the debt-to-asset ratio (DAR) on the risk of financial distress in energy sector companies in Indonesia. Firm size is used as a moderating variable, while gross domestic product (GDP) and interest rates serve as control variables. The study sample consists of 28 energy companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023, with a total of 105 observations. The analysis was conducted using panel data regression. The findings indicate that sustainability reports do not significantly influence financial distress. Conversely, DAR has a significant positive effect, indicating that the greater the proportion of debt to assets, the higher the risk of financial distress. Firm size does not strengthen or weaken the relationship between sustainability reports and financial distress, but plays a role in mitigating the negative impact of DAR on the risk. GDP and interest rates do not show a significant effect. The main limitation of this study lies in the variability and incompleteness of sustainability reports across companies. These findings highlight the importance of debt management and company scale in managing financial risk in the energy sector.